Desulfonylative Radical Truce–Smiles Rearrangement Utilizing the Benzimidazoline and Benzimidazolium Redox Couple - Miyajima, Ryo; Okamura, Manon; Oomori, Kazuki; Iwamoto, Hajime; Wakamatsu, Kan; Hasegawa, Eietsu (Synlett, 2023)
We have developed protocols for promoting redox reactions utilizing the 2-substituted 1,3-dimethylbenzimidazoline (BIH–R) and benzimidazolium (BI+–R) couples which were applied to the desulfonylative radical Truce–Smiles rearrangement. Expected rearrangement products formed in modest to good yields in these processes, in which added or in situ generated BIH–R serve as electron- and hydrogen-atom-donating reagents or photocatalysts. DFT calculations were carried out to gain the information about the radical intermediates involved in the rearrangement reaction.
Keywords: benzimidazoline and benzimidazolium redox couple; single-electron transfer; photoreducing catalyst; radical Truce–Smiles rearrangement; desulfonylative aryl migration